Analysis of Volatility and Turnover on the Disposition Effect in the Indonesian Stock Exchange - Rika Candraningrat, I; Salim, U; Khusniyah Indrawati, N; Ratnawati, K (KnE Social Sciences, 2018)
This study aims to analyse the influence of market turnover and volatility of the company on disposition effect. Disposition effect is the tendency of investors to quickly sell their shares to gain benefit (winner stock) and the tendency of investors to hold the stocks too long, which results in a loss (losing stocks). Identifying the causes of the disposition effect is important to determine whether the disposition effect makes the market inefficient. The population in this study is comprised of the companies registered in the LQ45 index in the Indonesian Stock Exchange during the period 2010–2015. The analytical method used is the linear regression analysis. Turnover has a positive and insignificant effect, while the volatility variable has a positive and significant effect on the behaviour of the disposition effect in Indonesia’s stock market. The characteristics of investors who perform disposition measures are likely to be risk averse if they are in a position of being profitable and risk-taking while in a position of loss. This is evident during the high volatility of the stock market. Large fluctuations such as significant price increases and drastic price reductions make investors in Indonesia take the right positioning of the right time in realizing profits and holding back losses. In this situation, the behaviour of investors who display the disposition effect in Indonesia’s stock exchange can be found. Keywords: behavioural finance, disposition effect, turnover, volatility